2004
DOI: 10.1074/jbc.m407950200
|View full text |Cite
|
Sign up to set email alerts
|

A Proteome-wide Approach Identifies Sumoylated Substrate Proteins in Yeast

Abstract: The ubiquitin-related protein SUMO-1 is covalently attached to proteins by SUMO-1 ligases. We have performed a proteome-wide analysis of sumoylated substrate proteins in yeast. Employing the powerful affinity purification of Protein A-Smt3 (Smt3 is the yeast homologue of SUMO-1) from yeast lysates in combination with tandem liquid chromatography mass spectrometry, we have isolated potential Smt3-carrying substrate proteins involved in DNA replication and repair, chromatin remodeling, transcription activation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
213
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(225 citation statements)
references
References 21 publications
9
213
3
Order By: Relevance
“…However, while HDAC sumoylation regulates a number of gene regulatory pathways in mammalian cells, in S. cerevisiae, proteomic analyses of sumoylated proteins indicate that HDACs are not a robust target (Wohlschlegel et al 2004;Zhou et al 2004;Hannich et al 2005), although Hda1 was detected in one SUMO proteomic analysis (Panse et al 2004). Our findings that substitution mutations in histone sumoylation sites increase transcription, and that SUMO fused to histones is repressive to transcription, strengthen the first two models of direct effect of histone sumoylation through either competition with acetylation or recruitment of HDACs (i.e., the first and second proposed mechanisms), rather than an indirect effect through altering HDAC activity (i.e., the third mechanism).…”
Section: Discussionmentioning
confidence: 99%
“…However, while HDAC sumoylation regulates a number of gene regulatory pathways in mammalian cells, in S. cerevisiae, proteomic analyses of sumoylated proteins indicate that HDACs are not a robust target (Wohlschlegel et al 2004;Zhou et al 2004;Hannich et al 2005), although Hda1 was detected in one SUMO proteomic analysis (Panse et al 2004). Our findings that substitution mutations in histone sumoylation sites increase transcription, and that SUMO fused to histones is repressive to transcription, strengthen the first two models of direct effect of histone sumoylation through either competition with acetylation or recruitment of HDACs (i.e., the first and second proposed mechanisms), rather than an indirect effect through altering HDAC activity (i.e., the third mechanism).…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 50 mammalian proteins are known as sumoylation targets (Hannich et al, 2005;Matunis et al, 1996). Global analyses in yeast and metazoans indicated >100 target proteins (Denison et al, 2005;Panse et al, 2004;Wykoff and O'Shea, 2005;Zhao et al, 2004;Zhou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Elimination of all three E3 activities (Siz1, Siz2, and Mms21) is synthetically lethal (Reindle et al 2006). While recent proteomic studies demonstrated that several hundreds of proteins can be modified in vivo (Panse et al 2004;Wohlschlegel et al 2004;Zhou et al 2004;Denison et al 2005;Hannich et al 2005;Wykoff and O'Shea 2005), direct evidence of biological significance and/or functional importance of these modifications is lacking for most substrates. Two main obstacles prevent the elucidation of the sumoylation's role for a given target protein using straightforward biochemical or genetic methods.…”
Section: Introductionmentioning
confidence: 99%